Effect of nano-sized bioactive glass particles on the angiogenic properties of collagen based composites - Vargas, Gabriela E.; Haro Durand, Luis A.; Cadena, Vanesa; Romero, Marcela; Vera Mesones, Rosa; Mackovic, Mirza; Spallek, Stefanie; Spiecker, Erdmann; Boccaccini, Aldo R.; Gorustovich, Alejandro A. (Journal of Materials Science: Materials in Medicine, 2013)
Angiogenesis is essential for tissue regeneration and repair. A growing body of evidence shows that the use of bioactive glasses (BG) in biomaterial-based tissue engineering (TE) strategies may improve angiogenesis and induce increased vascularization in TE constructs. This work investigated the effect of adding nano-sized BG particles (n-BG) on the angiogenic properties of bovine type I collagen/n-BG composites. Nano-sized (20-30 nm) BG particles of nominally 45S5 Bioglass composition were used to prepare composite films, which were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The in vivo angiogenic response was evaluated using the quail chorioallantoic membrane (CAM) as an model of angiogenesis. At 24 h post-implantation, 10 wt% n-BG containing collagen films stimulated angiogenesis by increasing by 41 % the number of blood vessels branch points. In contrast, composite films containing 20 wt% n-BG were found to inhibit angiogenesis. This experimental study provides the first evidence that addition of a limited concentration of n-BG (10 wt%) to collagen films induces an early angiogenic response making selected collagen/n-BG composites attractive matrices for tissue engineering and regenerative medicine. © Springer Science+Business Media New York 2013.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.effect

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Microstructure of veneered zirconia after surface treatments: A TEM study - Grigore, Alexandra; Spallek, Stefanie; Petschelt, Anselm; Butz, Benjamin; Spiecker, Erdmann; Lohbauer, Ulrich (Dental Materials, 2013)
Signcance. Regardless of the treatment protocol and produced roughness, the veneering ceramic perfectly sealed the zirconia surface. XRD showed an increased amount of monoclinic phase on the surface treated zirconia. However after thermal treatment, the monoclinic phase was re-transformed into the tetragonal polymorph. TEM/SAED analysis has found indication for a greater extend of the monoclinic transformation into the bulk zirconia compared to the treatment related defective zone depth. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Y-TZP; X-ray diffraction; Martensitic transformation; Sandblasting; Bur drilling; Annealing

PVP a binder for the manufacture of ultrathin ITO/polymer nanocomposite films with improved electrical conductivity - Wegener, Carsten Moritz; Kato, Minato; Kakimoto, Ken-Ichi; Spallek, Stefanie; Spiecker, Erdmann; Roosen, Andreas (Journal of Materials Science, 2015)
This paper presents the manufacture of ultrathin (< 1 A mu m) transparent conductive indium tin oxide (ITO) films based on nanoparticulate ITO slurries by the profile rod technique using the binder polyvinyl pyrrolidone (PVP) as an organic additive. The influence of the slurry composition on the film thickness and the specific electrical resistance as well as the transmission of the dried films is evaluated. The organic solvent ethanol and different types of the PVP binder were tested for slurry preparation and layer performance. ITO green films with low specific electrical resistance of 3 Omega cm, 87 % inline transmission, and layer thicknesses of only 250 nm could be manufactured. Furthermore, the influence of heat treatments up to 400 A degrees C on the electrical properties of the ITO films was evaluated.

Solution-Processed Metallic Nanowire Electrodes as Indium Tin Oxide Replacement for Thin-Film Solar Cells - Krantz, Johannes; Richter, Moses; Spallek, Stefanie; Spiecker, Erdmann; Brabec, Christoph (Advanced Functional Materials, 2011)
Solution processed silver nanowire (Ag NW) films are introduced as transparent electrodes for thin-film solar cells. Ag NW electrodes were processed by doctor blade-coating on glass substrates at moderate temperatures (less than 100 degrees C). The morphological, optical, and electrical characteristics of these electrodes were investigated as a function of processing parameters. For solar-cell application, Ag NW electrodes with an average transparency of 90% between 450 and 800 nm and a sheet resistivity of 10 O per square were chosen. The performance of poly(3-hexylthiophen-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) solar cells on Ag NW electrodes was found to match the performance of otherwise identical cells on indium tin oxide. Overall, P3HT:PCBM solar cells with an efficiency of 2.5% on transparent Ag NW electrodes have been realized.
Keywords: silver nanowires; electrodes; organic electronics; indium tin oxide replacement; solar cells

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors - Thiemann, Stefan; Sachnov, Swetlana; Gruber, Mathias; Gannott, Florentina; Spallek, Stefanie; Schweiger, Manuel; Krückel, Johannes; Kaschta, Joachim; Spiecker, Erdmann; Wasserscheid, Peter; Zaumseil, Jana (Journal of Materials Chemistry C, 2014)
We introduce a new type of silane-based ionogels that are produced by gelation of the ionic liquid 3-methyl-1-(3-(triethoxysilyl)propyl)-imidazolium bis(trifluoromethylsulfonyl)imide ([(EtO)3SiPMIM][TFSI]) with tetramethylorthosilane and formic acid. In the obtained ionogels the cations are involved in the network formation while the anions can move freely. The ionogels show advantageous properties for application in flexible electronics, such as low modulus, solution processability and high specific capacitance. Spray-coated ionogels were used as high capacitance gate dielectrics for organic (poly[3-hexylthiophene], P3HT) electrolyte-gated transistors (EGTs) that operated at very low voltages (<2 V) with high on/off ratios in air over weeks. Devices fabricated on polymer foil remained functional during repeated bending cycles with strains up to 2.3%.

Spray-Coated Silver Nanowires as Top Electrode Layer in Semitransparent P3HT:PCBM-Based Organic Solar Cell Devices - Krantz, Johannes; Stubhan, Tobias; Richter, Moses; Spallek, Stefanie; Litzov, Ivan; Matt, Gebhard; Spiecker, Erdmann; Brabec, Christoph (Advanced Functional Materials, 2013)
Silver nanowire (Ag NW) thin films are investigated as top electrodes in semitransparent inverted organic solar cells. The performance of semitransparent poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) organic solar cells with Ag NW top electrode layers is found to match very closely the performance of reference devices based on thermally evaporated, highly reflective metal silver top electrodes. The optical losses of the semitransparent electrodes are investigated in detail and analyzed in terms of transmission, scattering, and reflection losses. The impact on an external back reflector is shown to increase the light harvesting efficiency of optically thin devices. Further analysis of transparent devices under illumination from the indium tin oxide (ITO) backside and through the Ag NW front electrode open the possibility to gain deep insight into the vertical microstructure related devices performance. Overall, Ag NW top electrodes are established as a serious alternative to TCO based electrodes. Semitransparent devices with efficiencies of over = 2.0% are realized.
Keywords: silver nanowires; electrodes; semitransparent photovoltaic devices; organic electronics; spray deposition